2012 50th Annual Allerton Conference on Communication, Control, and Computing (Allerton) 2012
DOI: 10.1109/allerton.2012.6483427
|View full text |Cite
|
Sign up to set email alerts
|

Energy-delay tradeoffs in a load-balanced router

Abstract: Abstract-The Load-Balanced Router architecture has received a lot of attention because it does not require centralized scheduling at the internal switch fabrics. In this paper we reexamine the architecture, motivated by its potential to turn off multiple components and thereby conserve energy in the presence of low traffic.We perform a detailed analysis of the queue and delay performance of a Load-Balanced Router under a simple random routing algorithm. We calculate probabilistic bounds for queue size and dela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…No centralized scheduling is required by the load-balanced router architecture at the internal switch fabrics. Andrews & Zhang (2012) reconsidered the architecture with the motive of increasing potential without using manifold components. As a result the energy has conserved in the presence of small traffic and showed a thorough analysis of the queue.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…No centralized scheduling is required by the load-balanced router architecture at the internal switch fabrics. Andrews & Zhang (2012) reconsidered the architecture with the motive of increasing potential without using manifold components. As a result the energy has conserved in the presence of small traffic and showed a thorough analysis of the queue.…”
Section: Related Workmentioning
confidence: 99%
“…A load-balanced router under a simple random routing algorithm has shown the delay performance. The probabilistic bounds for queue size and delay showed that the probabilities drop exponentially with increasing queue size or time delay (Andrews & Zhang, 2012). Now-a-days, distributed virtual environments (DVEs) are widely adopted in recent years because of rapid growth of applications like massive multiplayer online games.…”
Section: Related Workmentioning
confidence: 99%